2021
DOI: 10.1002/er.7041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic on the enhancement of heat transfer for pulsating heat pipe

Abstract: Summary The pulsating heat pipe (PHP) has become one of the most promising devices to dramatically remove heat for electronic devices. This work focuses on the experimental investigation of ultrasonic on the enhancement of heat transfer of PHP, and further discusses this effect at the different working fluids. The results indicate that the external region of PHP exhibits more intense oscillation motion of working fluids than that of internal‐region. The heat transfer performance enhanced assisted with the ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Cao et al [14] designed a PHP coupled with Phase Change Materials (PCMs) for heat storage research, PHP as a heat tr ansfer medium, solved the problems of low thermal conductivity of PCMs and heat loss during heat transfer, an d accelerated the PCMs heat storage. Zhang et al [15] studied the effect of the coupling of ultrasonic waves and different working fluids on the heat transfer coefficient. PHP with acetone as the working fluid obtained a heat transfer coefficient of 1.85 times at a heating power of 15W; the heat transfer coefficient of the acetone-filled P HP is more stable with the assistance of ultrasound.…”
Section: Instructionmentioning
confidence: 99%
“…Cao et al [14] designed a PHP coupled with Phase Change Materials (PCMs) for heat storage research, PHP as a heat tr ansfer medium, solved the problems of low thermal conductivity of PCMs and heat loss during heat transfer, an d accelerated the PCMs heat storage. Zhang et al [15] studied the effect of the coupling of ultrasonic waves and different working fluids on the heat transfer coefficient. PHP with acetone as the working fluid obtained a heat transfer coefficient of 1.85 times at a heating power of 15W; the heat transfer coefficient of the acetone-filled P HP is more stable with the assistance of ultrasound.…”
Section: Instructionmentioning
confidence: 99%
“…The results showed that when methanol was the filling working medium, the optimal filling rate was 0.3. Zhang et al 12 studied the heat transfer efficiency of PHP under ultrasonic field. The experimental results show that ultrasonic cavitation effectively enhances the heat transfer efficiency of PHP.…”
Section: Introductionmentioning
confidence: 99%